Tunicamycin inhibits colon carcinoma growth and aggressiveness via modulation of the ERK-JNK-mediated AKT/mTOR signaling pathway - You, Shuping (Mol Med Rep, 2018)
Epidemiology and evidence have demonstrated that colon carcinoma is one of the most common gastrointestinal tumors in the clinic. Reports have suggested that Tunicamycin significantly inhibits aggressiveness of colon carcinoma cells by promotion of apoptosis. In the present study, the inhibitory effect of tunicamycin on colon cancer cells and the potential underlying molecular mechanism was investigated. Western blotting, immunohistochemistry, apoptotic assays and immunofluorescence were used to analyze the therapeutic effects of tunicamycin on apoptosis, growth, aggressiveness and cell cycle of colon tumor cells, by downregulation of fibronectin, vimentin and E-cadherin expression levels. In vitro experiments demonstrated that tunicamycin significantly inhibited growth, migration and invasion of colon carcinoma cells. In addition, tunicamycin administration promoted apoptosis of colon carcinoma cells via upregulation of apoptotic protease activating factor 1 and cytochrome c expression levels, which are proteins that have a role in mitochondrial apoptosis signaling. Cell cycle assays revealed that tunicamycin suppressed proliferation and arrested S phase entry of colon carcinoma cells. Mechanistic analysis demonstrated that tunicamycin reduced expression and phosphorylation levels of extracellular signal-regulated kinase (ERK), c-JUN N-terminal kinase (JNK) and protein kinase B (AKT), and inhibited mammalian target of rapamycin (mTOR) expression levels in colon carcinoma cells. Endogenous overexpression of ERK inhibited tunicamycin-mediated downregulation of JNK, AKT and mTOR expression, which further blocked tunicamycin-mediated inhibition of growth and aggressiveness of colon carcinoma. In vivo assays revealed that tunicamycin treatment significantly inhibited tumor growth and promoted apoptosis, which led to long-term survival of tumor-bearing mice compared with the control group. In conclusion, these results suggested that tunicamycin may inhibit growth and aggressiveness of colon cancer via the ERK-JNK-mediated AKT/mTOR signaling pathway, and suggested that tunicamycin may be a potential anti-cancer agent for colon carcinoma therapy.